2011
DOI: 10.1089/ars.2010.3645
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Shear Stress Induces Mitochondrial Superoxide Production: Implication of NADPH Oxidase and c-Jun NH2-Terminal Kinase Signaling

Abstract: Fluid shear stress is intimately linked with vascular oxidative stress and atherosclerosis. We posited that atherogenic oscillatory shear stress (OSS) induced mitochondrial superoxide (mtO 2 À ) production via NADPH oxidase and c-Jun NH 2 -terminal kinase ( JNK-1 and JNK-2) signaling. In bovine aortic endothelial cells, OSS (AE3 dyn=cm 2 ) induced JNK activation, which peaked at 1 h, accompanied by an increase in fluorescein isothiocyanate-conjugated JNK fluorescent and MitoSOX Red (specific for mtO 2 À produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…OSS also increases oxidative stress through enhanced NOX expression and activity. Takabe et al (40) demonstrated that OSS increased the generation of cytoplasmic O 2 Ϫ through NADPH oxidase activation, which consequently increased mitochondrial O 2 Ϫ through a JNK-dependent mechanism in EC. Consistent with these observations, we demonstrate a role for NOX contributing to enhanced cytoplasmic and mitochondrial ROS production, leading to enhanced NF-B activity underlying the RAGE activation in our model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OSS also increases oxidative stress through enhanced NOX expression and activity. Takabe et al (40) demonstrated that OSS increased the generation of cytoplasmic O 2 Ϫ through NADPH oxidase activation, which consequently increased mitochondrial O 2 Ϫ through a JNK-dependent mechanism in EC. Consistent with these observations, we demonstrate a role for NOX contributing to enhanced cytoplasmic and mitochondrial ROS production, leading to enhanced NF-B activity underlying the RAGE activation in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these observations, we demonstrate a role for NOX contributing to enhanced cytoplasmic and mitochondrial ROS production, leading to enhanced NF-B activity underlying the RAGE activation in our model. Although the specificity of apocynin as an inhibitor of NOX is controversial and may vary by cell type, it has been widely used in mechanistic studies of shear mediated NOX activity in endothelium both in vivo and in vitro (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 NF-E2-related factor 2 (Nrf2) is one of the major transcription factors in laminar flowmediated cytoprotective responses in ECs (3)(4)(5). Flow activation of Nrf2 induces a group of antioxidant genes via the activation of antioxidant response element (ARE) (3,6).…”
mentioning
confidence: 99%